Thorstein Veblen: suas influências, críticas e contribuições para a construção de uma ciência econômica evolucionária - Krauzer, Fernando Cavalheiro (2019)
This work aims at exploring the construction of Thorstein Veblen's evolutionary economic science, paying particular attention to his influences, critiques and theoretical contributions. Veblen, one of the founding fathers of the Original Institutional Economy, is known to be one of the most celebrated economists from the late nineteenth century to the present day. This is justified and evidenced by his fundamental role in the elaboration and theorization of an evolutionary perspective in economic thought, considering the role of important concepts derived from philosophy and incipient psychology in the formalization of his ideas. Through the method of bibliographic research, we have the construction of this work through the following chapters: (i) introductory considerations highlighting objectives, justification and method; (i) biographical chapter with analysis of context and influences; (ii) chapter directed to the construction of critiques and commentaries on Veblen’s contemporary economic science; (iv) chapter devoted to the identification and analysis of important works in Veblen's evolutionary economic science; and, finally, (v) final considerations and future developments. In advance, the author's academic career is seen as turbulent and intense, having gone through prestígious universities, collaborating with the dissemination of his Institutional Economy. Among his main influences are the fundamental character of the evolutionary perspective of Charles Darwin and classical pragmatic philosophy, mainly through Charles Peirce, John Dewey and William James. Through his training and influences, Veblen developed and refined important concepts for his theory, among them: habits, instincts and institutions. He was the author of several criticisms and made a point of demonstrating his dissatisfaction with the economic theory of his time, having commented and evaluated the writings of important icons of economic thought, such as Gustav Schmoller, Karl Marx, Alfred Marshall and John Bates Clark, among others. Veblen was the author of several works, of which two seem to stand out when intends to understand his evolutionary economic science: The Theory of the Leisure Class (1899) and The Instinct of Workmanship and the State of the Industrial Arts (1914). In view of Veblen's dense trajectory, it is pointed out that this work does not exhaust the discussions tied to this important thinker, although retakes the important discussion about his theory and evolutionary objectives in economic science.